Poverty and Excess Length of Hospital Stay in Neonatal Opioid Withdrawal Syndrome. Issue 2 (March 2020) - Vesoulis, Zachary A.; Lust, Christopher E.; Cohlan, Barbara A.; Liao, Steve M.; Mathur, Amit M.
Abstract : Objectives: To study the impact of sociodemographic factors on length of stay (LOS) for infants with neonatal opioid withdrawal syndrome (NOWS) secondary to fetal opioid exposure. Methods: In this retrospective cohort study, we included term infants with NOWS, excluding those with other significant medical issues. Comprehensive clinical and sociodemographic data were collected. Multivariate regression modeling was used to identify factors which contributed to excess LOS, which was defined as the number of days beyond the standard monitoring and/or treatment protocol. Results: In all, 129 infants were identified; mean gestational age of 37.9 ± 1.3 weeks and mean body weight of 2880 ± 496 g. Among them, 68% of infants were exposed to opioids; 27% were exposed to methadone; and 67% required pharmacologic treatment. The degree of poverty was assessed using the Area Deprivation Index (ADI) based on the mother's address at the time of birth. Median LOS for treated infants was 23 days versus 8 days for those who did not need pharmacologic treatment. The median excess LOS was 4 days (range 0–24). Excess hospital days were strongly correlated with degree of deprivation in the mother's community ( r = 0.55, P < 0.01). ADI remained a strong predictor of excess LOS, even when controlling for pharmacologic treatment, placement in state's custody, race, and gestational age at birth. Conclusions: These results suggest poverty is associated with excess LOS and that early allocation of resources for at-risk families may help to reduce overall length of hospital stay.